2015
DOI: 10.1115/1.4031666
|View full text |Cite
|
Sign up to set email alerts
|

Atomized Dielectric Spray-Based Electric Discharge Machining for Sustainable Manufacturing

Abstract: A novel method of using atomized dielectric spray in micro-electric discharge machining (EDM) (spray-EDM) to reduce the consumption of dielectric is developed in this study. The atomized dielectric droplets form a moving dielectric film up on impinging the work surface that penetrates the interelectrode gap and acts as a single phase dielectric medium between the electrodes and also effectively removes the debris particles from the discharge zone. Single-discharge micro-EDM experiments are performed using thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In the study of atomized spray-based EDM machining, the claimed values of W e and K m were 36.61 to 212.62 and 17.71 to 53.16 respectively. 29 In the present study, the values of K m number are <57.7 and the values of W e are >10. These values differ from those reported in the study of Pattabhiraman et al (2015) 29 since the fluid properties, atomizer type, and pressure range in this study are different.…”
Section: Characterization Of the Atomised Spraymentioning
confidence: 47%
See 2 more Smart Citations
“…In the study of atomized spray-based EDM machining, the claimed values of W e and K m were 36.61 to 212.62 and 17.71 to 53.16 respectively. 29 In the present study, the values of K m number are <57.7 and the values of W e are >10. These values differ from those reported in the study of Pattabhiraman et al (2015) 29 since the fluid properties, atomizer type, and pressure range in this study are different.…”
Section: Characterization Of the Atomised Spraymentioning
confidence: 47%
“…36 Pattabhiraman et al obtained the values of W e and K m for dielectric droplets in EDM for ensuring to be in the spreading regime for different spray pressures. 29 In order to ensure the droplet-surface interaction to be in the spreading regime, the values of W e , R e , and K m are calculated with the above information for pressures of 1 bar, 2 bar, and 3 bar at 20 mm downstream distance (Shown in Table I). The mass flow rate of the atomized electrolyte is measured to 56 ml min −1 and spray length 20 mm is considered since the spray is impinged from the height of 20 mm.…”
Section: Characterization Of the Atomised Spraymentioning
confidence: 99%
See 1 more Smart Citation
“…Ahad Gholipoor (2015) carried out comparative study of wet, dry and near dry EDM of SPK steel and suggested wet EDM for rough machining and near dry EDM for finishing [57]. Arvind Pattabhiraman et al (2015) studied the near dry EDM using atomized spray of EDM oil and suggested that in spray EDM discharge energy increased by 37% and volume of material removed increased by 78% [60]. Krishnakant Dhakar et al (2016) utilized glycerin in near dry EDM and achieved promising results owing to high viscosity of the glycerin and better surface finish [74].…”
Section: Binary Phase Dielectric/ Near Dry Edmmentioning
confidence: 99%
“…15 It was observed that spray Electric Discharge Machining was more efficient in terms of high MRR in comparison to wet and dry Electric Discharge Machining, for all possible set of discharge parameters. 16 It was also stated that in comparison to other gases as dielectric medium, nitrogen plasma jet was most effective in increasing machining efficiency. 17 While the surface finish (Ra) obtained on machined parts by oxygen assisted DEDM was very low due to the fact that oxygen assisted EDM resulted in high MRR which means that the craters produced over the surface of the machined workpiece will be deeper and wider which results in poor surface finish.…”
Section: Introductionmentioning
confidence: 99%